Construction of the Malay cross-linguistic lexical task: a preliminary report - Yap, Ngee Thai; A. Razak, Rogayah; Haman, Ewa; Łuniewska, Magdalena; Daller, Jeanine Treffers (University of Reading, 2017)
This paper reports on the development of the Malay Crosslinguistic Lexical Task (LITMUS-CLT) following the initiative of the COST Action IS0804 to create parallel tasks assessing various aspects of language development in bilingual and multilingual children (Armon-Lotem, de Jong, & Meir, 2015). LITMUS-CLTs are picture naming and picture choice tasks assessing receptive and expressive knowledge of single nouns and verbs. CLTs are created according to the same criteria in each language individually with the use of a common picture database. The development of the Malay CLT follows the procedure designed within the COST Action IS0804 with the modifications required for a new language in the sample of CLT languages. To that end, two preparatory studies with adult native speakers of Malay were conducted: a picture naming study using CLT picture base and a subjective age of acquisition (AoA) survey for words obtained in the picture naming study. The results of the two studies show that although Malay is typologically distant from languages included so far in the CLT sample, patterns similar to previous studies were obtained: nouns had higher naming agreement than verbs and AoA for all words was within the range of three to nine years (Łuniewska, et al., 2016).